SISTEM REKOMENDASI PEMINJAMAN BUKU DENGAN METODE USER-BASED COLLABORATIVE FILTERING PADA PERPUSTAKAAN SEKOLAH BERBASIS WEBSITE - Sirwan Sirwan; Pasnur Pasnur; A Sumardin; Annisa Nurul Putri; Mashud Mashud (LPPM Unbaja, 2023)
Book Lending Recommendation System Using User-Based Collaborative Filtering Method in Website-Based School Libraries.The purpose of this research is to design and implement a Book Lending Recommendation System with User-Based Collaborative Filtering Method in School Libraries. This data was obtained through: 1) Observation, 2) Interview, 3) Documentation. By using the User-Based Collaborative Filtering method in making this application. In making this application the User-Based Collaborative Filtering method is used to make recommendations based on book ratings given by library members.The results of this study indicate that the application of the Book Lending Recommendation System at the website-based school library with the User-Based Collaborative Filtering method is declared feasible to use with the percentage results on the testing aspects with a percentage rate of 84% getting a good response.